New-onset psychosis following COVID-19 vaccination: a systematic review - Lazareva, Marija; Renemane, Lubova; Vrublevska, Jelena; Rancans, Elmars (Frontiers in Psychiatry, 2024)
Background: The emergence of a new coronavirus strain caused the COVID-19 pandemic. While vaccines effectively control the infection, it's important to acknowledge the potential for side effects, including rare cases like psychosis, which may increase with the rising number of vaccinations. Objectives: Our systematic review aimed to examine cases of new-onset psychosis following COVID-19 vaccination. Methods: We conducted a systematic review of case reports and case series on new-onset psychosis following COVID-19 vaccination from December 1st, 2019, to November 21st, 2023, using PubMed, MEDLINE, ClinicalKey, and ScienceDirect. Data extraction covered study and participant characteristics, comorbidities, COVID-19 vaccine details, and clinical features. The Joanna Briggs Institute quality assessment tools were employed for included studies, revealing no significant publication bias. Results: A total of 21 articles described 24 cases of new-onset psychotic symptoms following COVID-19 vaccination. Of these cases, 54.2% were female, with a mean age of 33.71 ± 12.02 years. Psychiatric events were potentially induced by the mRNA BNT162b2 vaccine in 33.3% of cases, and psychotic symptoms appeared in 25% following the viral vector ChAdOx1 nCoV-19 vaccine. The mean onset time was 5.75 ± 8.14 days, mostly reported after the first or second dose. The duration of psychotic symptoms ranged between 1 and 2 months with a mean of 52.48 ± 60.07 days. Blood test abnormalities were noted in 50% of cases, mainly mild to moderate leukocytosis and elevated C-reactive protein. Magnetic resonance imaging results were abnormal in 20.8%, often showing fluid-attenuated inversion recovery hyperintensity in the white matter. Treatment included atypical antipsychotics in 83.3% of cases, typical antipsychotics in 37.5%, benzodiazepines in 50%, 20.8% received steroids, and 25% were prescribed antiepileptic medications. Overall, 50% of patients achieved full recovery. Conclusion: Studies on psychiatric side effects post-COVID-19 vaccination are limited, and making conclusions on vaccine advantages or disadvantages is challenging. Vaccination is generally safe, but data suggest a potential link between young age, mRNA, and viral vector vaccines with new-onset psychosis within 7 days post-vaccination. Collecting data on vaccine-related psychiatric effects is crucial for prevention, and an algorithm for monitoring and treating mental health reactions post-vaccination is necessary for comprehensive management.